Pesantren dan Kemandirian Perekonomian: Studi tentang Kewirausahaan di Pondok Pesantren Ar-Risalah Cijantung IV Ciamis - Zaini Hafidh; Badrudin Badrudin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This study is set forth from the existence of pesantren as the oldest educational institution in Indonesia which plays a central role within the socio-cultural environment construction of Indonesian society. In order to exist, today, the pesantren should be able to develop its intitution yet still maintaining its originality as the characteritics of the pesantren itself. The development strategy could be initiated through self-sustaining efforts which in fact bring a positive impact for pesantren. On the other hand, financial problems often threatens the existence of pesantren. The purpose of this research is to investigate the condition of boarding school Ar-Risalah Cijantung IV and economic initiatives developed by the boarding school. This research is a case study by employing qualitative approach. Data collecting techiques are done by interviews, observation and document study. The study found that economic initiatives that is conducted by the pesantren are livestock breeding, fishery, mining, agriculture and waste processing. Those initiatives have a positive impact on pesantren because they serve as other funding sources to support pesantren development without fully depend on government support. Those businesses also brought a positive impact for the community in the surrounding pesantren.